ผลของการอยู่ร่วมกันของราอาบัสคูลาร์ไมคอร์ไรซาและแบคทีเรียที่ช่วยส่งเสริมความสัมพันธ์แบบไมคอร์ไรซาต่อการเจริญเติบโตของอ้อย - ภัทราวรรณ ธีฆัมพร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Nowadays, the alternative ways for replacement of the use of chemical fertilizer and pesticides are strongly encouraged because of increasing claims of environmentally friendly and healthy agriculture. Biofertilizer using soil microorganisms such as arbuscular mycorrhizal fungi (AMF) and beneficial bacteria is a promising tool for sustainable agriculture. The aims of this study were to isolate and identify arbuscular mycorrhizal fungi (AMF) and mycorrhization helper bacteria and to determine the effects of AMF and mycorrhization helper bacteria on sugarcane seedlings. Eighteen different mycorrhizal spores were isolated from the sugarcane rhizosphere soils collected from various sugarcane fields in Thailand. The result in morphological observation found 3 families, namely Glomeraceae, Acaulosporaceae and Gigasporaceae and the population of the family Glomeraceae were found most dominant in the rhizosphere of sugarcane plants. AMF isolate AY01 and isolate AT04 were able to produce and increase their spores in sorghum roots with a large number of spores. AMF isolate AY01 and isolate AT04 were belonging to Diversispora using morphology and molecular technique based on 18S rRNA gene. One hundred and twenty-two bacterial isolate were isolated from AMF spores and were screened for their plant growth promoting (PGP) activities. The results showed 20 bacterial isolates had at least four PGP activities such as IAA, siderophore, ammonia and biofilm production or phosphate solubilization. Only one bacterial isolate, ATR16 was able to stimulate both spores of AMF isolate AY01 and isolate AT04. MHB isolate ATR16 was identified as Acinetobacter baumannii based on molecular technique. An experiment was conducted to determine the effect of selected AMF isolates, AY01 and AT04, and MHB isolate ATR16. The results revealed that shoot height, above and belowground biomass and root colonization of AMF in sugarcane seedlings inoculation with the combination of AMF and mycorrhization helper bacteria were significantly higher than the non-inoculated seedlings and sole inoculated seedlings. AMF isolate AY01 + MHB isolate ATR16 treatment was found the greatest increasing growth of the plants and the highest root colonization (69.48%). These results of this study indicate the synergistically interacting between AMF and PGP activities can enhance the growth of sugarcane seedlings and arbuscular mycorrhiza development. These findings could be useful for the development of bioinoculants suitable for the establishment of sustainable agriculture.